The Effect of Inflation, Bi Rate, JUB, Exchange Rate, and SBIS on the Jakarta Islamic Index in 2010-2023 - Sari, Yesi Rafika; Syah, Farid Ardyan (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: Despite variations in economic indicators such as inflation, central bank interest rates, monetary supply, currency valuations, and Islamic financial products, the Jakarta Islamic Index maintains steady stock trading performance. The study examines how various economic factors influenced the Jakarta Islamic Index (JII) between 2010 and 2023. In particular, it explores how the index's behavior is shaped by inflationary pressures, Bank Indonesia's benchmark rate, money circulation, foreign currency exchange rates, and Islamic-compliant certificates issued by Bank Indonesia.Design/Method/Approach: The study utilizes quantitative methods, analyzing data collected over time from credible institutions such as Bank Indonesia, the Financial Services Authority, the Central Statistics Agency, and other reputable sources. Various analytical approaches are employed, including classical assumption testing, multiple linear regression, individual and collective significance evaluations, and determination coefficient analysis. This research employs various analytical techniques to examine how multiple economic variables (including inflation rates, the Bank Indonesia interest rate, money supply levels, currency exchange rates, and Bank Indonesia Sharia Certificates) potentially influence or correlate with the performance of the Jakarta Islamic Index.Findings:The study's results indicate that among the economic factors analyzed, such as Inflation, BI Rate, Money Supply, and Bank Indonesia Sharia Certificates, most did not show significant individual effects on the Jakarta Islamic Index. The exchange rate, however, emerged as the only factor with a notable individual impact. Collectively, when all these economic variables were considered together, they were found to have a combined influence on the Jakarta Islamic Index.Originality/Values: This study's findings offer valuable information for both investors and policymakers, shedding light on the intricate workings of the Islamic capital market and pinpointing crucial economic factors that shape its performance.ABSTRACTPurpose: Despite variations in economic indicators such as inflation, central bank interest rates, monetary supply, currency valuations, and Islamic financial products, the Jakarta Islamic Index maintains steady stock trading performance. The study examines how various economic factors influenced the Jakarta Islamic Index (JII) between 2010 and 2023. In particular, it explores how the index's behavior is shaped by inflationary pressures, Bank Indonesia's benchmark rate, money circulation, foreign currency exchange rates, and Islamic-compliant certificates issued by Bank Indonesia.Design/Method/Approach: The study utilizes quantitative methods, analyzing data collected over time from credible institutions such as Bank Indonesia, the Financial Services Authority, the Central Statistics Agency, and other reputable sources. Various analytical approaches are employed, including classical assumption testing, multiple linear regression, individual and collective significance evaluations, and determination coefficient analysis. This research employs various analytical techniques to examine how multiple economic variables (including inflation rates, the Bank Indonesia interest rate, money supply levels, currency exchange rates, and Bank Indonesia Sharia Certificates) potentially influence or correlate with the performance of the Jakarta Islamic Index.Findings:The study's results indicate that among the economic factors analyzed, such as Inflation, BI Rate, Money Supply, and Bank Indonesia Sharia Certificates, most did not show significant individual effects on the Jakarta Islamic Index. The exchange rate, however, emerged as the only factor with a notable individual impact. Collectively, when all these economic variables were considered together, they were found to have a combined influence on the Jakarta Islamic Index.Originality/Values: This study's findings offer valuable information for both investors and policymakers, shedding light on the intricate workings of the Islamic capital market and pinpointing crucial economic factors that shape its performance.